Efektivitas Kampanye Politik di Instagram Untuk Mempengaruhi Niat Memilih - Magdalena Sola Gracia (COMMENTATE: Journal of Communication Management, 2020)
This study is conducted effectiveness of political campaign through Instagram as a social media to influence vote intention among Millenials in Indonesia. The study is performed with a quantitative approach and gathered data from 99 respondents that is a citizen of Bandung and eligible to vote. The findings revealed that four variables that influence the quality of the social media political campaign, namely content quality, the informality of speech, design, and frequency of post have the significant and positive influence to vote intention. However, among these variables, the most significant and positive influence belongs to design. It seems related to the nature of Instagram as photo-based social media.